Status of postgraduate training in the livestock sector in southern Africa and priorities for ILRI’s support - Dube, Sikhalazo (International Livestock Research Institute, 2009)
One of the five objectives of ILRI’s Capacity Strengthening Strategy is to facilitate building sustainable capacity of institutes to build capacity. This could only be achieved through building the capacity of the agricultural higher learning institutes and by facilitating the effective integration of research-based learning outputs (tools, methods and approaches) into the curricula of the learning institutes. In order to establish the priorities for collaborative capacity strengthening activities of the learning institutes in the areas of animal production and veterinary services, ILRI commissioned five studies covering the following subregions: Eastern and Central Africa (ASARECA region); Southern Africa (SADC region), West Africa (CORAF region); South Asia; and Southeast Asia. This report summarizes the findings of the gap analysis study for the Southern Africa (SADC) region. ILRI will make every effort to share and validate these findings and use this information in designing and implementing capacity strengthening activities in this region.